Relation of meteorological elements and air pollutants to respiratory diseases - Tombácz, Szintia; Makra, László (Acta Geographica Debrecina Landscape & Environment series, 2007)
This paper determines the characteristic weather types over the Carpathian Basin for the summer – early autumn period (July 15 – October 15) and the winter months (December, January, and February), with the levels of chemical (CO, NO, NO2 , NO2/NO, O3, O3max, SO2, PM10) and biological [Ambrosia (ragweed) pollen] air pollutants, and with their effect to the respiratory diseases. Based on the ECMWF data set, daily sea-level pressure fields analysed at 00 UTC (Coordinated Universal Time) were prepared for each weather type (cluster) in order to detect the relation between, on the one hand, the sea-level pressure patterns and, on the other, the levels of the chemical and biological air pollutants as well as the frequency of the respiratory diseases in Szeged. Objective definition of the characteristic weather types occurred by using the methods of Factor Analysis and Cluster Analysis. As a result, in the summer – early autumn period the total patient number is proportional to the mean monthly temperature, the maximum and minimum temperatures; however, respiratory diseases occur more frequently, when relative humidity is low. On the other hand, in the winter months there is no relation between the meteorological variables and the patient numbers.